Metallothionein 1B attenuates inflammation and hepatic steatosis in MASH by inhibiting the AKT/PI3K pathway - Canghai Guan; Xinlei Zou; Wujiang Shi; Jianjun Gao; Chengru Yang; Yifei Ge; Zhaoqiang Xu; Shaowu Bi; Xiangyu Zhong (Journal of Lipid Research)
Metabolic dysfunction–associated steatohepatitis (MASH) is a severe form of metabolic dysfunction–associated fatty liver disease metabolic dysfunction-associated steatohepatitis , characterized by hepatic steatosis, inflammation, and fibrosis. This study investigates the role and potential mechanisms of metallothionein 1B (MT1B) in MASH through bioinformatics analysis and experimental validation. quantitative reverse transcription PCR and Western blot analyses confirm that MT1B expression is significantly downregulated in liver tissues of MASH patients, in high-fat diet–induced mouse models, and in hepatocytes induced by FFAs. Further functional experiments show that upregulation of MT1B reduces intracellular triglycerides and total cholesterol levels, lipid droplet formation, and proinflammatory factors. In vivo experiments demonstrate that specific downregulation of hepatic MT1B expression via AAV8-shMT1B injection significantly increases triglyceride and total cholesterol levels, exacerbates lipid accumulation, and markedly elevates liver fibrosis and inflammatory factor expression. RNA-seq and bioinformatics analyses show that the AKT/PI3K pathway is significantly suppressed in MT1B-overexpressing cells. Further experiments indicate that AKT inhibition can reverse the lipid metabolism disorders and inflammatory responses caused by MT1B downregulation. Additionally, Zinc can promote the nuclear translocation of MTF1, leading to its binding to the MT1B promoter, thereby upregulating MT1B expression and ultimately mitigating MASH progression. These findings suggest that zinc-regulated MT1B plays a critical role in lipid metabolism and inflammatory responses by regulating the AKT/PI3K signaling pathway, influencing MASH progression.